The RECK tumor-suppressor protein binds and stabilizes ADAMTS10 - Matsuzaki, Tomoko (Biol Open, 2018)
The tumor suppressor protein RECK has been implicated in the regulation of matrix metalloproteinases (MMPs), NOTCH-signaling and WNT7-signaling. It remains unclear, however, how broad the spectrum of RECK targets extends. To find novel RECK binding partners, we took the unbiased approach of yeast two-hybrid screening. This approach detected ADAMTS10 as a RECK-interactor. ADAMTS10 has been characterized as a metalloproteinase involved in fibrillin-rich microfibril biogenesis, and its mutations have been implicated in the connective tissue disorder Weill-Marchesani syndrome. Experiments in vitro using recombinant proteins expressed in mammalian cells indicated that RECK indeed binds ADAMTS10 directly, that RECK protects ADAMTS10 from fragmentation following chemical activation and that ADAMTS10 interferes with the activity of RECK to inhibit MT1-MMP. In cultured cells, RECK increases the amount of ADAMTS10 associated with the cells. Hence, the present study has uncovered novel interactions between two molecules of known clinical importance, RECK and ADAMTS10. This article has an associated First Person interview with the first author of the paper.